Exploring the Role of Supply Chain Ambidexterity in Enhancing Resilience and Sustainability: A Mediated Framework - Alharbi, Ahmad A.; Sheta, Ibrahim H.; Mahgoub, Ibrahim G. (Journal of Posthumanism, 2025)
In an era of increasing global market volatility and frequent disruptions, the strategic importance of embedding resilience and sustainability into supply chain management has become paramount. Existing literature has established the benefits of supply chain ambidexterity (SCAMB)—the concurrent pursuit of exploitative and explorative strategies—to balance efficiency with adaptability. However, the mechanisms through which SCAMB impacts sustainable performance across economic, social, and environmental dimensions remain insufficiently explored. This study addresses this gap by investigating the mediating role of supply chain resilience (SCRES) in the relationship between SCAMB and sustainable performance. A quantitative research approach was adopted, involving the distribution of structured questionnaires to managers within a diverse set of manufacturing firms in Egypt. The analysis was conducted using structural equation modelling (SEM) to examine the hypothesised relationships. The findings confirm that both exploitative and explorative dimensions of SCAMB significantly contribute to SCRES, which in turn mediates their impact on sustainable performance. While SCRES enhances environmental and social sustainability outcomes, its influence on economic sustainability appears limited, suggesting that resilience-building may entail short-term costs that challenge immediate economic gains. The results advance the theoretical discourse by elucidating the indirect role of SCRES in translating ambidextrous strategies into sustainable outcomes. For practitioners, these findings underscore the necessity of strategically balancing exploration and exploitation to develop resilience that aligns with long-term sustainability objectives. The study’s implications call for further examination into sector-specific variations and the integration of digital technologies as facilitators of SCAMB and SCRES to achieve comprehensive sustainable performance.